Child Bullying Crimes (Islamic Perpective) - Haniyah, Haniyah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Bullying crime is a crime against humanity, it is a violation of human rights, a crime of bullying is an action taken because of an imbalance in the strength of the victim there are four elements in the crime of bullying, an element of power imbalance, imbalance to hurt (desire to heart), an existence threat, terror. There are several factors that cause children to commit bullying crimes including the influence of internal factors and extraterrestrial factors. In the view of Islam, bullying is an act that is prohibited by religion, because it contains elements of humiliating other people, and makes them feel wronged, children as perpetrators of bullying according to the child protection law and the juvenile justice system can be used. criminal sanctity as adults, Islam itself is very concerned about children, the rights of children in detail in Islam, so it is impossible for children who get a good education from parents, according to Islamic teachings are able to commit crimes, for that in Islam's view a child who commits a crime bullying cannot be sanctioned until they are of age